1981
DOI: 10.1104/pp.68.4.899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfhydryl Reagents on the Biophysical Properties of the Plasmalemma of Chara corallina

Abstract: The administration of the sulfhydryl reagent N-ethyl-maleimide (NEM) to internodal cells of Chara coralina caused alterations in the biophysical properties of the plasmalemma, as measured with electrophysiological and radioactive tracer techniques. The membrane potential depolarized to, or near, the calculated Nermst potential for potassium (EK) after 30 seconds' exposure to 0.1 millimolar NEM. During this time, the ATP level did not decrease below the control value, and the specific membrane resistance did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Thus, this NEM-induced reduction in the linear component is still consistent with uptake by facilitated diffusion. However, PCMBS has also been shown to depolarize the membrane potential to the K+ diffusion potential (22,23), and PCMBS had no effect on the linear component in high-salt roots, while consistently stimulating the linear component by 40% in low-salt roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this NEM-induced reduction in the linear component is still consistent with uptake by facilitated diffusion. However, PCMBS has also been shown to depolarize the membrane potential to the K+ diffusion potential (22,23), and PCMBS had no effect on the linear component in high-salt roots, while consistently stimulating the linear component by 40% in low-salt roots.…”
Section: Discussionmentioning
confidence: 99%
“…Although the linear component was relatively insensitive to sulfttydryl reagent inhibition, increasing exposures of NEM did result in a reduction of the linear component. NEM has been shown to depolarize the membrane potential to a level presumed to be the diffusion potential for K+ (22,23). This depolarization would reduce the driving force for passive K+ influx.…”
Section: Discussionmentioning
confidence: 99%
“…A brief exposure of Chara cells to NEM results in an opening of K+ channels within the plasmalemma (12). Thus, in our NEM-pretreated cells, the membrane potential would have been depolarized from -250 mv down to -150 mv (12).…”
Section: Cm-2 S-lmentioning
confidence: 99%
“…8) shown to open the K+ channels in the plasmalemma of Chara (12). Since Lichtner et al (12) did their experiments at pH 8.0, we exposed cells to NEM at both pH 8.0 and 6.5. Cells that were given 1-or 2-min pretreatment in 0.1 mm NEM had 'Cl-influx values similar to those of the controls (Table II).…”
Section: Cm-2 S-lmentioning
confidence: 99%
“…4), perhaps by inhibiting an ATPase proton pump in the same way it affects uptake by plant cells (Giaquinta, 1979;Lichtner, Lucas & Spanswick, 1981). Indeed Beale (1992) has shown that PCMBS is a potent inhibitor of ATPase in a plasma membrane fraction from Phytophthora cactorum (Lebert & Cohn), a related member of the Peronosporales.…”
Section: Assimilation By P Viciae Hyphaementioning
confidence: 99%